SHADOWING TECHNIQUE IMPROVE STUDENTS’ LISTENING SKILL IN CAPTURING THE WORD HEARD - Dedeh Auliatul Latifah; Maman Suryaman (PROJECT (Professional Journal of English Education), 2022)
Listening plays an important role in completing the other four skills in language class. Listening skills should need more attention because they have quite serious problems that are being experienced by students. In learning listening, students still find it difficult to master this skill naturally. One of the difficulties of students in performing listening skills is due to limited vocabulary so that they are unable to conclude the message conveyed by native speakers. The limitation of vocabulary is the main problem of many factors causing failure in listening class. In the process of activities in the listening class, they often fail to recognize the words that are heard and when that happens, they will stop to think about the word, resulting in falling behind from the next recording, eventually their focus will be destroyed. So, the research aims to prove how successful students are in capturing words with the shadowing technique, so that it can be said that the shadowing technique is a solution for both teachers and students in the listening class. This type of research is classroom action research called CAR consist four main parts of classroom action research such as planning, action, observation, and reflection.  The research subjects were 27 students. The methods used to collect data are observation and test. The results of the study were the average value from 73.2 to 77.0 in cycle I to cycle II. The percentage of students on the average score that has been obtained proves to have increased from 59% to 78%. Keywords:  Shadowing Technique, Listening Skill, Teaching, and Learning